Environmental analysis of a necropolis area in Frederico Westphalen, RS - Borba, Willian Fernando de (2020)
Environmental problems in graveyard areas are a major issue in contemporary society. Usually located in areas of low economic value and with no previous environmental statute, this activity may result in serious public health complications, mostly related to poisoning of the soil and groundwater bodies. In this regard, the present study conducted a survey of the existing graves in the municipal graveyard of Frederico Westphalen - RS, located in the northwest portion of the Rio Grande do Sul state. This survey ocurred through in loco data collection of the following information: Number, tipe (mausoleum, direct contact with the soil or above the soil), and state of conservation. The preliminary results point to a graveyard area of approximately 4.11 hectares, 2.377 graves, being 991 mausoleums, 1.115 above-ground graves and 271 with direct contact with the soil. Of those three, the one in wich the casket has direct contact with the soil poses a greater threat of poisoning, because of the leaking of necrochorume to the external medium. It is then concluded that the graveyard in general presents some graves where there is direct contact of the body with the soil, but it is important to note that this is in the older area, and this kind of burial is not done anymore. In this sense, is recomended the adoption of the criteria listed in the Resolution of the National Environment Council nº 335/2003” wich dispose on the procedures to the environmental licensing of graveyards, witch involves hydrogeological studies of the medium.